FAKTOR PENDUKUNG KEMENANGAN PASANGAN SYAMSUAR-ALFEDRI DI KAMPUNG SAWIT PERMAI KECAMATAN DAYUN DALAM PEMILIHAN KEPALA DAERAH KABUPATEN SIAK TAHUN 2015 - Yuswan, Baginda Alam; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The election of the regional head is the general election to elect the candidate for the regional leader which is directly implemented by the local people as a form of democracy at the local level. In the election of district head of Siak district in 2015, the pair of Syamsuar-Alfedri again won the election as regent and vice regent of Siak district period 2016-2021. Another phenomenon is where the pair of Syamsuar-Alfedri who is a candidate pair of malay background, able to excel in an area dominated by the transmigration village with the majority of the population background of the tribe of java. Based on the phenomenon that occurs then the formulation of the problem in this research is what factors supporting the victory of the couple Syamsuar-Alfedri in the village of palm Permai Dayun subdistrict in the election of district head of Siak district in 2015.This study aims to find out what factors supporting the victory of the couple Syamsuar-Alfedri in the village of palm Permai district Dayun in the election of district head of Siak district in 2015. This research uses qualitative method with descriptive research type. Data collection techniques are interviews and documentation. Informants of this research is a team of successful partners of Syamsuar-Alfedri community leaders, and members of political parties in the village of palm Permai.Based on the results of the study indicate that the factors supporting the victory of the pair of Syamsuar-Alfedri in the village of palm Permai subdistrict Dayun in the election of district head of Siak district in 2015 is the issues and policies, social imagery, emotional feelings, candidate personality, current events, personal events, and epistemic issues.Keywords : Election head, factors supporting the victory, voting behavior